Home Range and Movement Pattern of the Broad-Snouted Caiman (Caiman latirostris) in a Silviculture Dominated Landscape - Marques, Thiago Simon (2020)
Information on the home range and movement patterns of Neotropical crocodilians is scarce for most species, despite being essential for developing management and conservation plans. The broad-snouted caiman (Caiman latirostris) is a Neotropical crocodilian with a wide geographical distribution in South America. This species inhabits artificial reservoirs (e.g., small weirs) in silvicultural areas. However, its use of space in such circumstances is still unknown. The present study aims to estimate home range and movement patterns of the broad-snouted caiman in a silviculture-dominated landscape in São Paulo state, southeastern Brazil. Eight adult caimans (four males and four females) were monitored by radiotelemetry (GPS-UHF system) from February 2010 to October 2011. The collected position points were used to estimate home range sizes and movement patterns. Mean home range size (± SD) of all individuals was 96.6 ± 183.9 ha and 43.2 ± 78.6 ha estimated by Minimum Convex Polygon (MPC) and 95% Kernel Density Estimate methods (KDE), respectively, without difference between the sexes. Individual mean daily movement was 37.6 ± 18.6 m/d, being greater during the reproductive period. The surrounding matrix formed by Eucalyptus plantations was relatively permeable to caiman movement. The present results suggest that the wide variation in the home range size of the broad-snouted caiman could be a result of the space-time distribution of resources and social interactions. Further, variations in environment temperature and reproductive activities can influence the movement pattern of the species. Future studies of crocodilians in agricultural landscapes should prioritize other dimensions possibly related to space use such as agricultural practices of the matrix, water contamination by agrochemicals, and hunting pressures.